2016
DOI: 10.1017/s0022215116009191
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorder in otolaryngology: systematic review

Abstract: Initial temporomandibular disorder treatment steps can be undertaken by the otolaryngologist, with consideration of referral to dentists, oral and maxillofacial surgeons, or physiotherapists if simple pharmacological treatment or temporomandibular disorder exercise fails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The odds ratio of suffering from tinnitus among patients with TMDs was 4.45 [20]. Similar findings were observed by Stephan et al, who further concluded that ENT symptoms were found to be more common in patients who presented myofascial pain and less in those with intra-articular disc disorder [21]. Majersio et al (2016) evaluated frequency of otological symptoms and its association with TMD and concluded that 68% had ear symptoms, 44% had fullness of ear, and 37% had impaired hearing [22].…”
Section: Prevalence Of Cross Symptomssupporting
confidence: 82%
See 2 more Smart Citations
“…The odds ratio of suffering from tinnitus among patients with TMDs was 4.45 [20]. Similar findings were observed by Stephan et al, who further concluded that ENT symptoms were found to be more common in patients who presented myofascial pain and less in those with intra-articular disc disorder [21]. Majersio et al (2016) evaluated frequency of otological symptoms and its association with TMD and concluded that 68% had ear symptoms, 44% had fullness of ear, and 37% had impaired hearing [22].…”
Section: Prevalence Of Cross Symptomssupporting
confidence: 82%
“…As proposed by Stephan et al, 21 Red Flag symptoms which include emotional or psychological stress, medication usage, vertebrobasilar insufficiency, upper cervical spine instability, cardiac diseases, central neurological dysfunction, cranial nerve dysfunction, extreme weight changes, and concurrent infection should be evaluated and identified in patients with otological and TMD symptoms to look for any alternate diagnosis. Radiographic investigations include conventional TMJ radiography such as transcranial, transpharyngeal, and transorbital views, which however give limited information for diagnosis of TMD.…”
Section: Vol 5 | Issue 2 | Apr -Jun 2020mentioning
confidence: 99%
See 1 more Smart Citation
“…10 These symptoms are more common in patients with myofascial disturbance than in those with intraarticular disc disorder, possibly because of the shared embryonic origin of masticatory muscles and some middle ear structures. 11 Physical examination should include thorough palpation of the TMJ and masticatory muscles, noting any abnormal mandibular movement, tenderness and signs of bruxism. Normal jaw opening values are 35-45 mm; a value less than 25 mm suggests dysfunction with no translation occurring within the joint.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…In most patients with chronic musculoskeletal pain a peripheral anatomical cause for pain cannot be identified. For example, myofascial TMD is more commonly associated with stress and anxiety than anatomical pathology 40 while 90% of all chronic low back pain is diagnosed as 'non-specific' 18 . In conditions where a structural impairment can be detected (i.e.…”
Section: Introductionmentioning
confidence: 99%